Protocol for a randomized controlled trial: efficacy and mechanisms of dual-target anodal tDCS in post-stroke cognitive impairment - Xue, Xiayan; Zhang, Sicong; Guo, Qingjuan; Wu, Jiali; Zhang, Jingjing; Wang, Cong; Shan, Chunlei (Frontiers in Human Neuroscience, 2025)
BackgroundPost-stroke cognitive impairment (PSCI) significantly hinders functional recovery and quality of life in stroke survivors. Although transcranial direct current stimulation (tDCS) has emerged as a promising non-invasive neuromodulation technique to improve cognitive function, conventional single-target tDCS approaches often yield inconsistent outcomes across cognitive domains.MethodsThis randomized controlled trial aims to investigate the efficacy and underlying neural mechanisms of dual-target anodal tDCS (a-tDCS) in individuals with PSCI. Sixty participants will be randomly assigned to either a dual-target stimulation group or a single-target stimulation group. Each group will receive 10 sessions of tDCS over two weeks. Cognitive performance will be assessed using the Montreal Cognitive Assessment (MoCA) as the primary outcome, while secondary outcomes include the digit span test, Trail Making Test, and modified Barthel Index. Functional near-infrared spectroscopy (fNIRS) will be used to assess cortical activation and functional connectivity before and after the intervention.DiscussionThe findings are expected to provide evidence on the efficacy and underlying mechanisms of dual-target tDCS in PSCI rehabilitation, potentially offering a more effective neuromodulatory intervention strategy for cognitive recovery in stroke survivors.Clinical trial registrationhttp://www.chictr.org.cn, identifier ChiCTR2500096896.